Stabilization of a residual soil using calcium and magnesium hydroxide nanoparticles: A quick precipitation method - Yong L.L.; Perera S.V.A.D.N.J.; Syamsir A.; Emmanuel E.; Paul S.C.; Anggraini V. (MDPI AG, 2023)
The current study examines the potential of using calcium and magnesium hydroxide nanoparticles synthetized through a quick precipitation method as soil stabilizers for improving the engineering properties of tropical residual soil. The engineering properties of untreated and nanoparticles-treated soil were studied by carrying out a series of geotechnical tests including compaction, Atterberg limits, falling head permeability, and unconfined compressive strength (UCS). The stabilization mechanisms associated with soil-chemical reactions were further explored by performing microstructural analyses such as x-ray diffraction (XRD), variable-pressure scanning electron microscope (VP-SEM), and energy-dispersive x-ray spectroscopy (EDX). The findings revealed that the calcium hydroxide and magnesium hydroxide nanoparticles improved the geotechnical properties of residual soils in terms of reduced hydraulic conductivity and increased UCS. The percentage reduction of the hydraulic conductivity of magnesium and calcium hydroxide nanoparticles-treated soils compared to untreated soil after seven weeks of permeation were 85.14% and 98.70%, respectively. The magnesium and calcium hydroxide nanoparticles-treated soils subjected to 14 days of curing recorded a percentage increase in the UCS of 148.05% and 180.17%, respectively compared to untreated soil. Hence, it can be concluded that both magnesium and calcium hydroxide nanoparticles can be effectively utilized as environmental-friendly stabilizers. 2019 by the authors.